Unending dialectical politics of identity in Ethiopia [version 1; peer review: 2 approved] - Tefera Assefa (F1000Research)
Background Identity politics is one of political terminology which is subjected to continuous and increasingly contested conceptualization and use. Moreover, identity exists in all social level starting for individual to international level, which makes identity a multi-layer concept. There has been a great deal of identity-based terminological distortion and misconception in Ethiopian political discourses and practice since its formation in the modern form. One of the primary challenges in Ethiopian present political discourse is misconception, complexity, and contradiction between ethnic identity (የብሄር ማንነት) and civic identity or citizenship (የዜግነት ማንነት), which must be addressed in Ethiopian political discourse. Methods In this paper, critical post-modernism research philosophy and Dialectical Method is used to analyze the rotation of contradiction between Pan-Ethiopianism and Pan-ethnic nationalism. The narrative analysis is used to make a critical investigation of the vicious cycle unending dialectics of identity politics in Ethiopia. Discussion The current political situation is an indication of unending dialectics of Ethiopian politics. The existing politics of ethnic identity and citizenship indicate unending dialectic of political friction with the rotation of thesis and anti-thesis which left the state building projection of country incomplete and weak dialectical process. Wrong policy and political responses of successive regime to the nationality questions (quests for power sharing and autonomous self-government) resulted in the sustained and vicious circle of conflict. Conclusion Generally, it is argued that prescription of one side of nationalism at the expense of the other will never resolve the political crisis of the country. Therefore, it is recommended that both integrationist and accommodationist institutional design and multinational democratic federalism should be implemented effectively to cope with the salience of identity politics in the country.